2019
DOI: 10.3390/ma12050708
|View full text |Cite
|
Sign up to set email alerts
|

Overview and Future Advanced Engineering Applications for Morphing Surfaces by Shape Memory Alloy Materials

Abstract: The development of structures able to autonomously change their characteristics in response to an external simulation is considered a promising research field. Indeed, these structures, called smart structures, can be adopted to improve the aerodynamic performance of air and land vehicles. In this work, an overview and future applications of Shape Memory Alloys (SMA)-based smart structures are presented. The use of SMA materials seems to be very promising in several engineering sectors. Advanced SMA-based devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 115 publications
0
30
0
1
Order By: Relevance
“…The SMAs ought to have a martensite finish temperature well over the most extreme working temperatures (see the dark spotted lines in Figure 20) so as to work appropriately. The correlation of the change temperature scopes of the most widely recognized SMAs that the less expensive Cu-Al-Ni SMAs can play out the change with temperatures up to 200°C, however, these SMAs are fragile, unsteady, have low exhaustion quality and are not appropriate for numerous cyclic activities [106,113,[115][116][117][118][119]. A wide determination of high temperature SMAs are accessible, however, these materials are known as costly for automobile applications [113].…”
Section: Brief Applicability Of Cu-based Smasmentioning
confidence: 99%
“…The SMAs ought to have a martensite finish temperature well over the most extreme working temperatures (see the dark spotted lines in Figure 20) so as to work appropriately. The correlation of the change temperature scopes of the most widely recognized SMAs that the less expensive Cu-Al-Ni SMAs can play out the change with temperatures up to 200°C, however, these SMAs are fragile, unsteady, have low exhaustion quality and are not appropriate for numerous cyclic activities [106,113,[115][116][117][118][119]. A wide determination of high temperature SMAs are accessible, however, these materials are known as costly for automobile applications [113].…”
Section: Brief Applicability Of Cu-based Smasmentioning
confidence: 99%
“…As the actuators based on SMA have the advantages of simple structure, small size, light quality, and low cost, the SMA is increasingly used in different fields [2]. For example, advanced SMA-based devices have been designed to improve the aerodynamic performance of vehicles [3], to actuate light grippers and reusable non-explosive lock release mechanisms [4,5], and to generate constant force components [6], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory alloy (SMA) as a smart material has been the subject of intensive research in various areas, including robotics, micromechanical systems, the aerospace and automotive industries, civil structural engineering, and biomedical sciences [1][2][3][4]. A wide range of industrial applications are also found in medical stents, unmanned aerial vehicles (UAVs), A/C vents, and so forth [1,5,6]. Compared to conventional electromagnetic motor actuators, SMAs offer noiseless operation, design flexibility, and resistance to functional degradation from dust or humidity with compact system configurations.…”
Section: Introductionmentioning
confidence: 99%